2007
DOI: 10.1080/14734220601016080
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models of tremor

Abstract: This review focuses on rodent models of tremor, particularly those induced by pharmacological agents. Harmaline is one of the most frequently used tremor-generating drugs and harmaline-induced tremor is regarded as a model of essential tremor. Harmaline acts on inferior olive neurons, causing enhanced neuronal synchrony and rhythmicity in the olivocerebellar system. In addition, it selectively induces cerebellar Purkinje cell death, speculatively because of excessive glutamate release from nerve terminals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 57 publications
2
65
0
Order By: Relevance
“…As previously described in this review, the inferior olive is a pacemaker of tremor rhythm for harmaline-induced tremor, and T-type Ca channels are specifically associated with neuronal oscillations induced by harmaline [10,31]. Next, oxotremorineinduced tremor is one of the cholinomimetic-induced tremors [22,24]. The actual tremor-generating mechanism underlying cholinomimetic-induced tremor remains unknown; however, muscarinic receptors in the striatum may be the primary tremor-generating mechanism because local injection of cholinergic agonists directly into the striatum sufficiently produces tremors [32].…”
Section: Effect Of T-type Ca Channel Blockers On Experimental Tremorsmentioning
confidence: 94%
See 4 more Smart Citations
“…As previously described in this review, the inferior olive is a pacemaker of tremor rhythm for harmaline-induced tremor, and T-type Ca channels are specifically associated with neuronal oscillations induced by harmaline [10,31]. Next, oxotremorineinduced tremor is one of the cholinomimetic-induced tremors [22,24]. The actual tremor-generating mechanism underlying cholinomimetic-induced tremor remains unknown; however, muscarinic receptors in the striatum may be the primary tremor-generating mechanism because local injection of cholinergic agonists directly into the striatum sufficiently produces tremors [32].…”
Section: Effect Of T-type Ca Channel Blockers On Experimental Tremorsmentioning
confidence: 94%
“…They also reported that in mice lacking the Ca V 3.1 gene, harmaline failed to induce rhythmical, synchronous discharges in the inferior olive, which are closely associated with generation of tremor rhythm. In addition, they demonstrated that the tremor-suppression effect of the Ca V 3.1 knockdown was specific to harmaline-induced tremor but not other experimental tremors, such as those induced by oxotremorine, physostigmine, or penitrem A, of which the tremor generator is not the inferior olive [24]. These findings suggest that Ca V 3.1 channels play a specific role as a molecular pacemaker substrate for intrinsic neuronal oscillations of the inferior olive under harmaline-induced tremor conditions.…”
Section: T-type Calcium Channels In a Tremor-generating Mechanism Indmentioning
confidence: 96%
See 3 more Smart Citations